A meta‐analysis of mammographic screening with and without clinical breast examination. Issue 7 (17th June 2015) - Hamashima, Chisato; Ohta, Koji; Kasahara, Yoshio; Katayama, Takafumi; Nakayama, Tomio; Honjo, Satoshi; Ohnuki, Koji
<x xml:space="preserve">Abstract</x> Mammographic screening with clinical breast examination has been recommended in Japan since 2000. Although mammographic screening without clinical breast examination has not been recommended, its introduction is anticipated. The efficacies of mammographic screening with and without clinical breast examination were evaluated based on the results of randomized controlled trials. PubMed and other databases for studies published between 1985 and 2014 were searched. The study design was limited to randomized controlled trials to evaluate mortality reduction from breast cancer. Five studies were eligible for meta‐analysis of mammographic screening without clinical breast examination. The relative risk for women aged 40–74 years was 0.75 (95% confidence interval, 0.67–0.83). Three studies evaluated the efficacy of mammographic screening with clinical breast examination. The relative risk for women aged 40–64 years was 0.87 (95% confidence interval, 0.77–0.98). The number needed to invite was always lower in mammographic screening without clinical breast examination than in mammographic screening with clinical breast examination. In both screening methods, the number needed to invite was higher in women aged 40–49 years than in women aged 50–70 years. These results suggest that mammographic screening without clinical breast examination can afford higher benefits to women aged 50 years and over. Although evidence of the efficacy of mammographic screening without clinical breast examination was confirmed based on the results of the randomized controlled trials, a Japanese study is needed to resolve local problems.